A randomized controlled trial on the blood pressure–lowering effect of amlodipine and nifedipine‐GITS in sustained hypertension. Issue 5 (11th April 2019) - Huang, Qi‐Fang; Sheng, Chang‐Sheng; Li, Yan; Dou, Yu; Zheng, Mei‐Sheng; Zhu, Zhi‐Ming; Wang, Ji‐Guang; ,
Abstract: In a multicenter, randomized trial, we investigated whether the long half‐time dihydropyridine calcium channel blocker amlodipine was more efficacious than the gastrointestinal therapeutic system (GITS) formulation of nifedipine in lowering ambulatory blood pressure (BP) in sustained hypertension (clinic systolic/diastolic BP 140‐179/90‐109 mm Hg and 24‐hour systolic/diastolic BP ≥ 130/80 mm Hg). Eligible patients were randomly assigned to amlodipine 5‐10 mg/day or nifedipine‐GITS 30‐60 mg/day. Ambulatory BP monitoring was performed for 24 hours at baseline and 4‐week treatment and for 48 hours at 8‐week treatment with a dose of medication missed on the second day. After 8‐week treatment, BP was similarly reduced in the amlodipine (n = 257) and nifedipine‐GITS groups (n = 248) for both clinic and ambulatory (24‐hour systolic/diastolic BP 10.3/6.5 vs 10.9/6.3 mm Hg, P ≥  0.24) measurements. However, after missing a dose of medication, ambulatory BP reductions were greater in the amlodipine than nifedipine‐GITS group, with a significant ( P  ≤ 0.04) between‐group difference in 24‐hour (–1.2 mm Hg) and daytime diastolic BP (–1.5 mm Hg). In conclusion, amlodipine and nifedipine‐GITS were efficacious in reducing 24‐hour BP. When a dose of medication was missed, amlodipine became more efficacious than nifedipine‐GITS.